Energy and Environmental Performance Analysis of Biomass-fuelled Combined Cooling and Heating System for Commercial Building Retrofit: An Italian Case Study. (November 2016) - Moretti, Elisa; Barbanera, Marco; Foschini, Daniele; Buratti, Cinzia; Cotana, Franco
Abstract: This study focuses on the operating performance of a biomass boiler (100 kW) coupled with an absorption chiller machine at the service of a commercial building in central Italy. A detailed life cycle environmental assessment (LCA) was performed by comparing the biomass-fuelled system to conventional system, using the SimaPro software. To assess the environmental impact, experimental data, such as energy consumptions and emission factors of the biomass boiler, were used as input data. Biomass-fuelled system was found to have the lowest impact in cumulative energy demand (CED), global warming potential (GWP), and ReCiPe single score method.